Comparison of health behaviors of adult women in Korea before and during the COVID-19 pandemic: secondary analysis of the Korea National Health and Nutrition Examination Survey 2019-2020 - Mijong Kim; Hyunju Chae (Korean Society of Women Health Nursing, 2022)
Purpose This study investigated the changes in the health-related behaviors of adult women in Korea during the coronavirus disease 2019 (COVID-19) pandemic. Methods Data from the eighth Korea National Health and Nutrition Examination Survey (2019-2020) were analyzed. The participants were 4,848 women aged 19 to 64 years in 2019 and 2020. Data analysis using the complex sampling design was performed using SPSS 20.1. Results Positive changes during the pandemic compared to before the pandemic in Korean adult women were found for improved subjective oral health perceptions (odds ratio [OR], 1.77; p<.001), increased moderate-intensity exercise in work and leisure activities (OR, 1.75; p<.001 and OR; 1.29, p=.004), and a decrease in secondhand smoke exposure at the workplace and in public places (OR, 0.64; p=.004 and OR, 0.60; p<.001). However, the following negative health behavior changes were found: decreased frequency of walking 5 days a week (OR, 0.81; p=.011) and an increase in unhealthy daytime sleep durations (OR, 1.40; p=006). Conclusion Compared to before the COVID-19 pandemic, Korean adult women perceived their subjective dental health more positively during the COVID-19 pandemic, decreased their exposure to secondhand smoke at work and in public places, decreased walking, and increased sleep duration during the week. Since this study only compared data between 1 year before and after the start of the pandemic, it is necessary to investigate a longer period of time in the future. A future study should attempt to identify the factors related to changes in health behaviors caused by the pandemic.